Penerapan Remedial untuk Pembelajaran Cerpen Kelas VIII SMP Dharma Bakti St. Paulus Oelolok - Sisilia Seuk (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2018)
Remedy is education service given to the students to improve their learning achievement to get pass score criteria. This research aims at increasing students’ pass score of short story material at second grade students of junior high school Dharma Bakti St. Pulus Oelolok that is about twenty people. Research result shows that thirteen students or about 80 % get learning pass score while seven students or about 40 % in the opposite site. Then, those students who did not pass the score was given remedy at shape grouping material, make the story plot, and find background in the short story. Final result shows that five students or about 80 % are in good category and two students are in very good category. Furthermore, it can be concluded that remedy has positive effect that can increase motivation and learning achievement to get pass score.